AKIBAT HUKUM PENGAMBILALIHAN PERUSAHAAN ATAU AKUISISI TERHADAP STATUS PERUSAHAAN MAUPUN STATUS PEKERJA PADA PT (PERSEROAN TERBATAS) - Sudiartha, I Wayan; Novy Purwanto, I Wayan (Kertha Semaya : Journal Ilmu Hukum, 2014)
Corporate takeover or acquisition is a legal act performed by a legal entity or naturalperson to take over the company's shares , by way of purchase of shares or in part or in fullfrom the assets of the company company . Acquisition can be forced to occur ( unfriendlytakeover / hostile takeover ) and voluntary / friendly ( friendly takeover ) . The acquisitionhas several advantages that companies still use the old name and does not require a licensefor a new business . The method used in this paper is the normative method . Due to thelegal status of the company's acquisition of the company being taken over control of thecompany is switching of shares taken over , while the legal consequences of the status ofworker liability company that was taken over is not terminated unless agreed otherwise inthe takeover agreement , the working relationship between workers and employers will endif one party does not want anymore to cooperate with other parties.
Keywords: Legal Consequences, Corporate Takeover, Aquisition